Access restrictions to forest resources, rather than COVID-19 bans, drive the selection of firewood species for bonfires during Festas Juninas in northeastern Brazil - Iara Vitória de Oliveira Araújo; Diego Centeno-Alvarado; Marcelo Alves Ramos (BMC, 2024)
Abstract Background The complex interplay of social and environmental factors shapes ecosystems, potentially leading to harmony or conflict, highlighting the importance of understanding these dynamics for coexistence. In developing countries, firewood serves as a primary energy source and plays a role in cultural-religious rituals and festivities. However, the specific patterns of woody species used for the latter remain poorly understood, including the impact of access restrictions to resources and local bans on practices. Therefore, our research focuses on examining how access restrictions to forest resources and bonfire bans due to the coronavirus disease 2019 (COVID-19) impact the cultural-religious tradition of bonfire making during Festas Juninas (June festivities) in northeastern Brazil. Methods Ethnobotanical fieldwork was conducted in two rural populations in northeastern Brazil between 2021 and 2022. Data were collected through semi-structured interviews, observations, and the guided tour technique. The cultural-religious tradition of bonfire making (i.e., richness of native and exotic firewood species, firewood volume, and the number of bonfires related to this practice) was compared between populations (i.e., differing in access restrictions) and years (i.e., differing in COVID-19-related bans) using Mann-Whitney U tests. Results Results revealed significant differences in the richness of native (p value = 0.001) and exotic (p value < 0.001) firewood species for bonfire making due to access restrictions to forest resources. The number of native species used was higher among the population residing in the area with unrestricted access than among those with restricted access, while a greater number of exotic species was used in the population with restricted access. The rest of the variables were not influenced by access restrictions, and no variables were influenced by COVID-19 bans. Conclusions Our study demonstrated that access restrictions to forest resources, rather than COVID-19 bans, drive the selection of firewood species for bonfires during Festas Juninas in northeastern Brazil. In addition, as populations remain deeply entrenched in cultural-religious practices amid temporary bans imposed by health crises, there is a pressing need for culturally sensitive environmental policies. Fostering socio-ecological resilience demands a comprehensive approach that encompasses not only environmental factors but also cultural dimensions, which wield a pivotal influence on long-term sustainability.